2021
DOI: 10.1088/1361-6528/ac2dc3
|View full text |Cite
|
Sign up to set email alerts
|

The disappearance and return of nanoparticles upon low energy ion irradiation

Abstract: Ion irradiation of bulk and thin film materials is tightly connected to well described effects such as sputtering or/and ion beam mixing. However, when a nanoparticle is ion irradiated and the ion range is comparable to the nanoparticle size, these effects are to be reconsidered essentially. This study investigates the morphology changes of silver nanoparticles on top of silicon substrates, being irradiated with Ga+ ions in an energy range from 1 to 30 keV. The hemispherical shaped nanoparticles become conical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Recent studies on singly-charged low energy ions with nanorods and -cubes showed interesting, yet largely unexplored effects with regards to erosion and ion channeling. [18,19] In this study, we irradiate gold nanoislands grown on a MoS 2 monolayer [20,21] with single slow highly charged xenon ions. On a MoS 2 monolayer substrate the gold nanoislands are bound via van-der-Waals forces only, [21] which leads to a reduced thermal conductivity [22] and electronic coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on singly-charged low energy ions with nanorods and -cubes showed interesting, yet largely unexplored effects with regards to erosion and ion channeling. [18,19] In this study, we irradiate gold nanoislands grown on a MoS 2 monolayer [20,21] with single slow highly charged xenon ions. On a MoS 2 monolayer substrate the gold nanoislands are bound via van-der-Waals forces only, [21] which leads to a reduced thermal conductivity [22] and electronic coupling.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] Today, being in an era of nanotechnology, the irradiated object sizes are often comparable to the projected ion range, which led to the discovery of many new effects, as the situation is different to the ion irradiation of bulk or thin films. A reduced dopant incorporation, [27] an enhanced sputtering yield [28][29][30][31][32][33][34][35] as well as an enhanced dynamic annealing and thus lower damage formation [36][37][38] are a few of those effects, which recently opened the research field of "ion-nanostructureinteractions".…”
Section: Introductionmentioning
confidence: 99%